DYNAMICS OF PUBLISHING ESTONIAN, LATVIAN AND LITHUANIAN BOOKS IN THE FIRST HALF OF THE 19TH CENTURY: A COMPARATIVE ANALYSIS - Navickienė, Aušra (Knygotyra, 2016)
The article presents results of comparative analysis of book publishing statistics in Estonian, Latvian and Lithuanian languages in the 19th century. This study was conducted referring to the most representative sources at that moment – the national retrospective bibliographies of Estonian, Latvian and Lithuanian books. After the analysis of all the publications that had been published yearly from 1801 to 1855, the overall number of publications was then calculated in every country. Furthermore, the publishing rates were evaluated for every decade in the three countries and additionally rates of publications per 1,000,000 inhabitants over every decade were calculated and evaluated. The data presented in this article should be viewed as an initial stage for the comparative analysis of Estonian, Latvian and Lithuanian nineteenth century book publishing. Estonian, Latvian and Lithuanian nations grew by preserving the old national traditions and developing new targets for political existence. At the same time, Estonian, Latvian and Lithuanian books were becoming more modern. Even various restrictions on the rights of nations living in the lands occupied by the Russian Empire and the annihilation of cultural differences did not prevent their publishing evolution. However, in view of general growth trend, publishing development varied in different countries and was determined by economic, social and cultural features of each region. Compared to Lithuania, the environment for the development of national books was more friendly in Estonia and Latvia. After the analysis of all above-mentioned sources it was determined that over the period from 1801 to 1855, most publications were published in the Latvian language – 1846, almost eight hundred less in Estonian language, accounting for 1027, and almost twice less (three times less than Latvian), accounting for 644, in the Lithuanian language. Evidently, book publishing in national language in Lithuania fell significantly behind compared to Latvia and Estonia. It is also important to note that book development in all three countries was uneven and was undergoing periodic rises and falls. The analysis of publishing rates per 1,000,000 inhabitants over every decade showed that Estonia had the highest rate of the three Baltic countries researched. Estonian book publishing increased from 18 to 102 print units per year or rose five-times, whilst in Latvia it increased from 28 to 67 units or 2.3 times. In Lithuania, book publishing rates per 1,000,000 inhabitants over the 55-year period increased not that highly – from 6 to 16 print units per year. By contrast, this rise in publishing rates was 0.3 times higher than in Latvia. The results of this initial study could be used for continuing research of such nature. Bibliographic method, descriptive statistics (data collection, organisation and presentation) and comparative methods were employed to analyse quantitative volumes of publishing, whereas analytical and statistical methods could be used to verify the quantitative trends of the development of publishing and their breaking points. Analytical statistics methods, rarely used in the works of bibliographers, could provide new knowledge on the changes of publishing in percentage terms. At least some of the methods could be employed. For example, the join point method, which could help clarifying the qualitative development trends of publishing by a number of particular linear segments (periods) and points, setting essential changes of the phenomenon in order to identify a statistically relevant or irrelevant growth or decline in publishing in percentage terms, and to distinguish its breaking points. Another method is that of simple linear regression, which helps to calculate the average annual change in the number of publications in percentage terms and depict this in a graph. This trend of developing comparative studies of Estonian, Latvian and Lithuanian books may lead to qualitatively better results.